Mulberry leaf extract reduces damage by regulating the oxidative response, immune response and intestinal flora of largemouth bass (Micropterus salmoides) under chronic heat stress - Bing Fu; Donglai Zhou; Xiaotong Qiu; Jieqiu Zheng; Qiong Yang; Yang Xiao; Sentai Liao; Qingrong Li; Dongxu Xing (Frontiers in Marine Science, 2025)
Chronic heat stress (HS) induces oxidative damage, low immunity, and intestinal flora disturbance of fish, posing great challenges to the aquaculture industry. As an important plant extract, mulberry leaf extract (MLE) has been shown to have antioxidant and immune-boosting properties. This study evaluated the protective effect of dietary MLE on HS-induced liver injury and intestinal flora disturbance in Largemouth bass ( Micropterus salmoides ) based on oxidative damage parameters, immune parameters, and intestinal flora composition. Fish were randomly assigned into three groups: CON group (ambient temperature, 26°C, basal diet), HS group (33°C, basal diet), and HS + MLE group (33°C, basal diet supplemented with 9 g/kg MLE). HS significantly decreased the final body weight, specific growth rate, intestinal villus length, muscular layer thickness, ACE and Chao1 indices, and lipase, trypsin, total superoxide dismutase (T-SOD), glutathione peroxidase (GPx), alkaline phosphatase (AKP), and lysozyme (LZM) activities, but significantly increased the feed conversion rate, aspartate aminotransferase (AST) activity, reactive oxygen species (ROS), malondialdehyde (MDA), complement 3 (C3) contents, and the relative abundances of Proteobacteria and Plesiomonas . Compared with the HS group, dietary MLE significantly improved lipase, trypsin, GPx, ACP, and LZM activities, and ACE and Chao1 indices in intestine, but significantly decreased the numbers of vacuoles and inflammatory cells, AST activity, and the GLU, MDA, and ROS contents. Dietary MLE also significantly up-regulated the mRNA expressions of gpx , tg f-β , il-10 , jnk2 , and bcl-2 , but down-regulated the mRNA expressions of il-8 , tnf-α , caspase-3 , atf4 , chop , ire1, traf2 , jnk1 , TRPV , MCU , and VDAC in liver. In conclusion, dietary supplementation with 9 g/kg MLE could improve the growth, immunity, and diversity of intestinal flora in heat-stressed largemouth bass, and alleviate hepatic injuries by regulating inflammation, oxidative stress, and apoptosis, providing a theoretical basis for the development of MLE as a treatment against HS.